Pain Input After Spinal Cord Injury (SCI) Undermines Long-Term Recovery and Engages Signal Pathways That Promote Cell Death - Turtle, Joel D.; Strain, Misty M.; Reynolds, Joshua A.; Huang, Yung-Jen; Lee, Kuan H.; Henwood, Melissa K.; Garraway, Sandra M.; Grau, James W. (Frontiers in Systems Neuroscience, 2018)
Pain (nociceptive) input caudal to a spinal contusion injury increases tissue loss and impairs long-term recovery. It was hypothesized that noxious stimulation has this effect because it engages unmyelinated pain (C) fibers that produce a state of over-excitation in central pathways. The present paper explored this issue by assessing the effect of capsaicin, which activates C-fibers that express the transient receptor potential vanilloid receptor-1 (TRPV1). Rats received a lower thoracic (T11) contusion injury and capsaicin was applied to one hind paw the next day. For comparison, other animals received noxious electrical stimulation at an intensity that engages C fibers. Both forms of stimulation elicited similar levels of c-fos mRNA expression, a cellular marker of nociceptive activation, and impaired long-term behavioral recovery. Cellular assays were then performed to compare the acute effect of shock and capsaicin treatment. Both forms of noxious stimulation increased expression of tumor necrosis factor (TNF) and caspase-3, which promotes apoptotic cell death. Shock, but not capsaicin, enhanced expression of signals related to pyroptotic cell death [caspase-1, inteleukin-1 beta (IL-1ß)]. Pyroptosis has been linked to the activation of the P2X7 receptor and the outward flow of adenosine triphosphate (ATP) through the pannexin-1 channel. Blocking the P2X7 receptor with Brilliant Blue G (BBG) reduced the expression of signals related to pyroptotic cell death in contused rats that had received shock. Blocking the pannexin-1 channel with probenecid paradoxically had the opposite effect. BBG enhanced long-term recovery and lowered reactivity to mechanical stimulation applied to the girdle region (an index of chronic pain), but did not block the adverse effect of nociceptive stimulation. The results suggest that C-fiber input after injury impairs long-term recovery and that this effect may arise because it induces apoptotic cell death.